Characteristics of boli formed by dairy cows upon ingestion of fresh ryegrass, lucerne or chicory. (15th November 2018) - Minnee, E. M. K.; Waghorn, G. C.; Gregorini, P.; Bryant, R. H.; Chapman, D. F.
Abstract : This study examined the comminution of fresh herbage, subsequent nutrient release, and the characteristics of swallowed boli from three physically and chemically contrasting forages during ingestive mastication by dairy cows. The extent and pattern of nutrient release will determine their availability to rumen microflora, and potentially influence their efficiency of use. The forages evaluated were perennial ryegrass (ryegrass, Lolium perenne L., cv Alto AR37), lucerne ( Medicago sativa L., cv Torlesse) and chicory ( Cichorium intybus L., cv Choice). Experimental design was a 3×3 cross-over with three forages and three consecutive 1-day measurement periods, conducted twice. Six non-lactating, pregnant, multiparous Holstein-Friesian×Jersey cows ( Bos taurus ) were used, with the first cross-over applied to three mature (10.1±0.61 years old; BW 631±64 kg) cows, and the second to three young (4.8±0.02 years; BW 505±19 kg) cows. Fresh cut forage was offered to the cows following partial rumen evacuation. Swallowed boli were collected directly at the cardia at the commencement, middle and end of the first feeding bout of the first meal of the day. Forage species did not affect the fresh weight of ingested boli (mean 169 g, P =0.605) but the proportion of saliva in boli varied between forage. Boli of chicory contained the greatest amount of herbage material and least amount of saliva, whereas ryegrass boli were the opposite. Boli fresh weight tended to increase as time in the meal progressed, but the age of the cow was not shown to affect any boli characteristics or nutrient release. Particle size reduction was affected by forage, with 31%, 38% and 35% of chicory, lucerne and ryegrass herbage reduced to <2 mm. There was little evidence of relationship between comminution and any physical or chemical characteristic of the forage, except in ryegrass where extent of comminution was moderately correlated with herbage strength. Proportional release of herbage soluble carbohydrate exceeded that of N during mastication. Differences in loss of N were moderately correlated with the amount of N in the herbage ( R 2 =0.53) but herbage comminution was not strongly correlated with release of either N or carbohydrate. These findings illustrate the complex animal×forage interactions that occur during mastication, and that it is not possible to infer nutrient loss from herbage based on herbage characteristics as the driver for this differ between species.